A3.11 Selective deletion of cells expressing fibroblast activation protein attenuates synovial inflammation. (24th February 2016) - Croft, AP; Campos, J; MacKenzie, M; Filer, A; Fearon, DT; Barone, F; Buckley, CD
Abstract : Background and objectives: Fibroblasts are key effector cells of synovial inflammation and joint damage. Fibroblast activation protein (FAP) is a cell surface serine protease, expressed at a low level by synovial fibroblasts but which is significantly up-regulated during inflammation. Furthermore the levels of FAP expression in the human synovium correlate with disease persistence in patients with early synovitis and in mice FAP has been shown to protect against inflammation induced cartilage damage1. However, it remains unclear whether it is FAP itself, or specific cellular populations expressing FAP that play a major role in these processes. Materials and methods: To determine the role of FAP+ fibroblasts in arthritis, we utilised a transgenic mouse in which FAP expressing cells were ablated (FAP-DTR2) by administration of diphtheria toxin in either in a prophylactic or therapeutic regime. Inflammatory polyarthritis was induced by the passive transfer of K/BxN serum into naïve mice. Mice were scored for clinical signs of arthritis and flow cytometry of digested synovial tissue was performed to determine the expression of fibroblast subsets. Results: FAP was dynamically expressed by fibroblasts, with up-regulated expression observed during inflammation. In wild type mice, FAP was predominately expressed by lining layer synovial fibroblasts compared to sub-lining fibroblasts, and a subpopulation of FAP expressing cells also expressed Podoplanin. Prophylactic deletion of FAP+ cells before the transfer of serum resulted in delayed onset of inflammatory arthritis but with similar severity to control mice. In contrast, therapeutic deletion of FAP+ cells significantly attenuated both the clinical signs and severity of synovial inflammation. Conclusion: These data suggest a pathogenic role for FAP expressing fibroblasts in synovial inflammation. References: Wäldele S. Arthritis Res Ther. 2015;20: 17–12 Kraman M. Science. 2010;330(6005):827–830